The ABC of European Union law - Borchardt, Klaus-Dieter (Luxembourg Publications Office of the European Union, 2010)
The Lisbon Treaty entered into force on 1 December 2009, after being ratified by all 27 Member States of the European Union, and introduced changes to European law and institutions. The ABC of European Union law by Klaus-Dieter Borchardt examines the roots of the European project and its development as a legal order, and is a definitive reference work on the subject. The author offers insight into how the European Union is built, its broad principles and the legal order underpinning it, looking at this in relation to the national laws of the Member States. This book is intended for people with no specialist legal knowledge who wish to understand the implications of European law for their daily lives.